Bases of musical nationalism in Argentina - Fusco Morales, Andrea Gabriela (2023)
This collaboration is an adaptation to the format of scientific article of the contents of my doctoral thesis about Argentina’s Nationalism. It reflects on this movement in orchestral music and study the ways in which composers expressed it in their works by incorporating elements from folklore, indigenous music and tango. For a study of the musical corpus, we made a selection of representative works by several composers of the period and analyzed them based on the object of study. We established links between the observed features and the characteristics of folk, indigenous and urban popular music; we focus our attention on the ways in which artists crafted these elements with European tools. The construction of nationalism is a conscious decision that involves political, historical and cultural aspects. Towards the end of the 19th century and the first half of the 20th century, nationalism stood out in Argentina and in Latin America and the other countries. Artists trained in Europe returned to their homeland bringing not only tools for the composition of academic music, but also the innovations of the time. The first part of this article is based on the reasons for building the nationalist movement of Argentina. The analysis of score will be studied in a second part.